Design and development of thermosensitive rectal in situ gel from Luffa acutangula fruits for the treatment of ulcerative colitis - Barangule, Swati P.; Maru , Avish D. (Journal of Applied Pharmaceutical Research, 2024)
Background: Luffa acutangula has good anti-inflammatory and antioxidant activity.  Ulcerative colitis has inflamed intestinal mucosal lining with frequent diarrhoea, mucosal, and bloody stools. The rectal administration provides high bioavailability, rapid absorption, and instant therapeutic effect. Conventional rectal formulations may be painful, while insertion and discomfort may also be experienced from the rectum leakage. Methodology: Luffa acutangula fruit extract was used for the preparation a novel rectal mucoadhesive in situ-gel by using thermosensitive polymers such as Poloxamer 407, Poloxamer 188.  HPMC K4M and carbopol 940 are two mucoadhesive polymers that are used to boost the mucoadhesive force and gel strength. The response surface method design was used to optimize the formulation. The formulated in situ gel batches were analysed by gelation temperature, gel strength, gelling ability, gelling time, viscosity and in vitro drug release and mucoadhesive strength.  Results and Discussion:  The concentration of poloxamer 407 (15%) and poloxamer 188 (3%) was optimized by design expert. The optimized formulation F10 showed 36.35±0.890 gelation temperature and 94.66±0.57 % cumulative drug release. Drug release kinetics follows Higuchi release model and according to Korsemeyer Peppa's model value of n= 1.1114 indicates supercase -II transport. Gelation temperature of mucoadhesive in situ gel (F10HP2) was found in the range 36.45±0.102°C with 91.37±0.84 % cumulative drug release. Mucoadhesive in situ gel was tested in rat model of ulcerative colitis for 7 days. Conclusion: Preclinical study of optimized formulation shows that Luffa acutangula fruit extract can stop or prevent further progression of acetic acid induced ulcerative colitis in rat model.